Mechanism of von Willebrand factor scissile bond cleavage by a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13) - Xiang, Yaozu (National Academy of Sciences, 2011)
The platelet-tethering function of von Willebrand factor (VWF) is proteolytically regulated by ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13), which cleaves the Tyr1605-Met1606 (P1-P1′) bond in the VWF A2 domain. To date, most of the functional interactions between ADAMTS13 and VWF that have been characterized involve VWF residues that are C terminal to the scissile bond. We now demonstrate that the substrate P3 position in VWF, Leu1603, is a critical determinant of VWF proteolysis. When VWF Leu1603 was substituted with Ser, Ala, Asn, or Lys in a short VWF substrate, VWF115, proteolysis was either greatly reduced or ablated (up to 400-fold reduction in k(cat)/K(m)). As Leu1603 must interact with residues proximate to the Zn(2+) ion coordinated in the active center of ADAMTS13, we sought the corresponding S3 interacting residues. Substitution of 10 candidate residues in the metalloprotease domain of ADAMTS13 identified two spatially separated clusters centered on Leu198 or Val195 (acting with Leu232 and Leu274, or with Leu151, respectively), as possible subsites interacting with VWF. These experimental findings using the short VWF115 substrate were replicated using full-length VWF. It is hypothesized that VWF Leu1603 interacts with ADAMTS13 Leu198/Leu232/Leu274 and that Val195/Leu151 may form part of a S1 subsite. The recognition of VWF Leu1603 by ADAMTS13, in conjunction with previously reported remote exosites C terminal of the cleavage site, suggests a mechanism whereby the VWF P1-P1′ scissile bond is brought into position over the active site for cleavage. Together with recently characterized remote exosite interactions, these findings provide a general framework for understanding the ADAMTS family substrate interactions.